2015
DOI: 10.5377/nexo.v28i01.1779
|View full text |Cite
|
Sign up to set email alerts
|

La bioprecipitación de carbonato de calcio por la biota nativa como un método de restauración.

Abstract: RESUMENPartiendo de 30 aislados bacterianos de diferentes tipos (fundamentalmente Bacillus), previamente aislados e identificados por métodos microbiológicos y moleculares, provenientes de biopelículas epilíticas aisladas del Castillo de Chapultepec de la ciudad de México, DF. Se realizaron diferentes metodologías como comprobación de capacidad para formar biopelículas y su cuantificación, prueba de ureasa y la producción de cristales de carbonato de calcio en placa Petry con Luria Bertani enriquecido con carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Large biofilms were obtained, showing the potential to be used in crack filling purposes for increasing lifespan or preventing early deterioration. Similar results were reported by Páramo Aguilera et al, who found optimal biofilm formation by using B. subtilis and B. cereus bacterial strains [67].…”
Section: Microbiologically Induced Carbonate Precipitation On Solid Ssupporting
confidence: 90%
“…Large biofilms were obtained, showing the potential to be used in crack filling purposes for increasing lifespan or preventing early deterioration. Similar results were reported by Páramo Aguilera et al, who found optimal biofilm formation by using B. subtilis and B. cereus bacterial strains [67].…”
Section: Microbiologically Induced Carbonate Precipitation On Solid Ssupporting
confidence: 90%
“…Several studies reported self-healing of cracks of (<0.5 mm) by Bacillus cohnii, B. pseudofirmus, B. subtilis, B. alkalinitrilicus, Pseudomonas aeruginosa, and Diaphorobacter nitroreducens (Jonkers et al, 2010;Wang et al, 2012Wang et al, , 2014Ersan et al, 2015;Khaliq and Ehsan, 2016). Several studies have also been conducted in the restauration of historic monuments such as Thouars church tower (Le Metayer-Levrel et al, 1999;Tiano et al, 1999), Alcázar de Guadalajara (Jroundi et al, 2014), Angera Cathedral (Perito et al, 2014), and Castillo de Chapultepec (Aguilera et al, 2015) using MICP.…”
Section: Microbially Induced Calcium Carbonate Precipitation (Micp)mentioning
confidence: 99%
“…Noteworthy research endeavors have extensively explored the use of diverse microorganisms like B. subtilis, BKH4 (alkaliphilic bacterium), B. pseudofirmus, Bacillus cohnii, B. alkalinitrilicus, Diaphorobacter nitroreducens, Bacillus sphaericus, and Streptococcus aureus. These microorganisms have proven effective in repairing cracks that measure less than 0.5 mm, through their targeted and specialized activities (Aguilera, et al 2015;Adzami, et al 2018;Ersan, et al 2015;Jonkers, et al 2010;Jroundi, et al 2014;Khaliq, & Ehsan, 2016;Le Metayer-Levrel, et al 1999;Perito, et al 2014;Sarkar, et al 2019;Shukla, et al 2022;Tiano, et al 1999;Wang, et al 2012).…”
Section: What Aremicrobial-based Construction Materials?mentioning
confidence: 99%